A Rare Mullerian Duct Anomaly Not Included in the Classification System by the American Society for Reproductive Medicine. (21st March 2013) - Brown, Shereene J.; Badawy, Shawky Z. A.
Abstract : This is a case report of a 37-year-old female with a uterine septum (two cavities), a normal single fundal contour, two cervices, and a longitudinal vaginal septum. This is a rare finding that is not described in the current classification system by the American Society for Reproductive Medicine.